Development and Design of Network Security System Software Based on Big Data Analysis Technology. Issue 2 (August 2021) - Wang, Xiang; Li, Zheng; Hong, Haiming; Zhou, Minghui
Abstract: As an important part of the Internet field, big data has a wide range of applications in many fields. At present, neither study nor life can leave the network big data. But at the same time, issues related to network security have also attracted widespread attention from the public and professionals. Based on the knowledge of big data and computer network security, this article analyzes the threats to computer network security in the data age and discusses the development and design of relevant network security software.